Regarding the subjects of prevention of criminal offenses in the sphere of tourism activities of Ukraine - Nesterova, I. A. (Аналітично-порівняльне правознавство, 2025)
It is determined that the subjects of prevention of criminal offenses committed in the sphere of tourism services constitute a system of state bodies, officials, public organizations, social groups and individual individuals who direct their activities to identifying, eliminating and neutralizing the causes and conditions that determine the existence and reproduction of criminality in tourism in general and individual criminal offenses, as well as preventive influence on persons who are potentially prone to committing the specified criminal acts. It is proven that the analysis of the range of crime prevention subjects in tourism activities has shown their significant diversity. In the author’s opinion, the appropriate classification can be carried out according to several criteria. According to the criterion of belonging to state and non-state structures, the subjects of crime prevention there can be divided into state (law enforcement agencies, the State Tax Service of Ukraine, the State Customs Service, the State Service of Ukraine for Food Safety and Consumer Protection, judicial bodies, etc.) and non-state (professional associations of tourism entities and other public organizations, labor collectives, non-state media, etc.). Depending on the specifics of the actions committed in this sphere, prevention entities can be classified into: 1) entities of general competence that manage crime prevention activities, organize and coordinate them at the general social level; 2) entities of corruption prevention; 3) entities of fraud prevention; 4) entities of human trafficking prevention; 5) entities of tax evasion prevention. The author agrees with the opinion of researchers who classify crime prevention subjects by specialization (tasks, competence, and content of preventive activities) into specialized and non-specialized. The author notes that this complex process of crime prevention in this sphere of activity requires the joint work of all subjects of preventive influence. The role of each subject of preventive activity in the area under consideration is invaluable and their interaction is necessary to ensure the effective operation of the sphere and the sustainable development of tourism in Ukraine.